Post-acquisition performance of acquiring firms in the telecommunication industry,UK 2000-2010 - Jaicim, Harshil (2013)
I examine a sample of friendly takeovers in the telecommunication industry, in the UK from the period 2000 to 2010. An event study is carried out around the announcement date of acquisitions, and I calculate the abnormal returns to the acquiring firms in this event window. In particular, this study will go on to focus on the post-acquisition performance of the acquirer with regards to method of payment (cash and mixed acquisitions) and the industry relatedness between the acquiring and target firms.